2020
DOI: 10.4103/ijmr.ijmr_585_20
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for repurposing drugs for the coronavirus disease 2019

Abstract: The newly emerged 2019 novel coronavirus (CoV), named as severe acute respiratory syndrome CoV-2 (SARS-CoV-2), like SARS-CoV (now, SARS-CoV-1) and Middle East respiratory syndrome CoV (MERS-CoV), has been associated with high infection rates with over 36,405 deaths. In the absence of approved marketed drugs against coronaviruses, the treatment and management of this novel CoV disease (COVID-19) worldwide is a challenge. Drug repurposing that has emerged as an effective drug discovery approach from earlier appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 87 publications
(121 reference statements)
0
43
0
1
Order By: Relevance
“…Flavonoids. SARS-CoV-2 nucleic acid inhibitors, RdRp gene blockers and virus translation inhibitors and are some examples of drugs proposed for COVID-19 treatment [8].…”
Section: Therapeutic Targets For Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids. SARS-CoV-2 nucleic acid inhibitors, RdRp gene blockers and virus translation inhibitors and are some examples of drugs proposed for COVID-19 treatment [8].…”
Section: Therapeutic Targets For Covid-19 Treatmentmentioning
confidence: 99%
“…CYP blockers and 5. Immune response enhancers (nitazoxanide and interferons) are suggested for COVID-19 treatment [8].…”
Section: Therapeutic Targets For Covid-19 Treatmentmentioning
confidence: 99%
“…Ritonavir is a potent inhibitor of the metabolizing enzymes in vivo that are responsible for the extensive degradation of lopinavir. The co-administration of ritonavir boosts the activity of lopinavir by enhancing its exposure to virus and improves the antiviral activity 25 28 .…”
Section: Therapeutic Interventions and Prophylactic Measuresmentioning
confidence: 99%
“…Some compounds have been found as a potential treatment against SARS CoV-2 in many studies (Caly et al, 2020;Elmezayen et al, 2020;Hendaus, 2020;Zhou et al, 2020). There are studies in which antiviral drugs such as Anti-HIV, Anti-HCV, Anti-HBV and drugs for other infectious diseases have been suggested as therapies (Barlow et al, 2020;Bhatnagar et al, 2020;Cherian et al, 2020;Fan et al, 2020;Sayad et al, 2020). Some of them have suggested that combinations of drugs may provide rapid viral clearance than the single agent alone (Cao et al, 2020;Sheahan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%